An Offer You Can't Refuse? Incentives Change What We Believe - Sandro Ambuehl (Center for Economic Studies and ifo Institute (CESifo), 2017)
Much of economics assumes that higher incentives increase participation in a transaction only because they exceed more people's reservation price. This paper shows theoretically and experimentally that when information about the consequences is costly, higher incentives also change reservation prices to further increase participation. A higher incentive makes people gather information in a way that is more favorable to participation—as if they were persuading themselves to participate. Hence, incentives change not only what people choose, but also what they believe their choices entail. This result informs the debate about laws around the world that severely restrict incentives for transactions such as organ donation, surrogate motherhood, human egg donation, and medical trial participation. It helps bridge a gap between economists on the one hand and the policy makers and ethicists on the other.
Keywords: D03; D04; D84; 330; incentives; repugnant transactions; information acquisition; inattention; experiment